Usability Evaluation Of Virtual Umrah Based On User Centered Design From Expert User View - Azilawati, Rozaimee; Siti Dhalila, Mohd Satar; Wan Malini, Wan Isa; Wan Ismail, Wan Abdullah; Nazirah, Abd Hamid; Normala, Rahim (2015)
With the emergence of the learning materials volume, the developer has to face many challenges to develop an effective and efficient application to support the learning process. The objective of this study is to evaluate usability of Virtual Umrah application based on expert views using User-Centered Design approach. User-Centered Design is a multi-stages process that requires the designers to analyze and verify the requirement of a user by involving the user throughout the whole processes. The findings of the usability evaluations are for errors, efficiency and satisfaction level, the individual mean score is 4.00, 4.20 and 4.40. While for the memorability and learnability component, the mean score for the items are below than 4.00 which are 3.80 and 3.70 respectively. These findings demonstrate that the developed application is significantly needed by the pilgrims and individuals in order to assist them in preparation and performing Umrah